2014
DOI: 10.4012/dmj.2014-187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thione primers on adhesive bonding between an indirect composite material and Ag-Pd-Cu-Au alloy

Abstract: The current study evaluated the effect of primers on the shear bond strength of an indirect composite material joined to a silverpalladium-copper-gold (Ag-Pd-Cu-Au) alloy (Castwell). Disk specimens were cast from the alloy and were air-abraded with alumina. Eight metal primers were applied to the alloy surface. A light-polymerized indirect composite material (Solidex) was bonded to the alloy. Shear bond strength was determined both before and after the application of thermocycling. Two groups primed with Metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Therefore, bond strength evaluations alone are insufficient to reveal the effect of bonding agents on zirconia ceramics. Several techniques used in materials science and surface science to analyze the composition of solid surfaces can be used to determine the elemental composition, and studies using such techniques have been reported (11)(12)(13)(14). However, although many bond strength studies focused on bonding of zirconia ceramics have been performed under a variety of test and aging conditions, limited evidence is available on the chemical reaction between functional monomers and zirconia surfaces (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bond strength evaluations alone are insufficient to reveal the effect of bonding agents on zirconia ceramics. Several techniques used in materials science and surface science to analyze the composition of solid surfaces can be used to determine the elemental composition, and studies using such techniques have been reported (11)(12)(13)(14). However, although many bond strength studies focused on bonding of zirconia ceramics have been performed under a variety of test and aging conditions, limited evidence is available on the chemical reaction between functional monomers and zirconia surfaces (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The acetone washing time was based on that described in a previous study, which found that VTD spectra depended on acetone washing time (10). For MTU-6, the effectiveness of acetone washing was confirmed in a previous study, which reported that MTU-6 was strongly adsorbed onto an Ag-Pd-Cu-Au alloy surface, even after repeated acetone cleaning (8). Suzuki et al used SERS spectroscopy to analyze the structure of VTD adsorbed to a colloidal gold surface (9).…”
Section: Discussionmentioning
confidence: 63%
“…The bonding characteristics of MTU-6 are better than those of VTD (3,8,14,15). However, few studies have examined the characteristics of MTU-6 bonding to dental metal alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBB initiated methyl methacrylate (MMA) resins have been used for bonding enamel (1)(2)(3)(4), dentin (3,5), casting alloy (6)(7)(8), and ceramics (9)(10)(11) in combination with various etchants and primers.…”
Section: Introductionmentioning
confidence: 99%